Care ecosystem training: Developing a free online dementia course for a growing lay health workforce: Dementia care research (research projects; nonpharmacological) / Use of technologies. (7th December 2020) - Dulaney, Sarah; Allawala, Mahnoor; Thoma, Mark; Merrilees, Jennifer; Lynch, Shalini; Chodos, Anna H; Huffman, Sara; Chiong, Winston; Hooper, Sarah M; Possin, Kate L
Abstract: Background: The Care Ecosystem is a telephone‐based dementia care program that is delivered by trained lay heath workers called Care Team Navigators (CTNs) who are supported and supervised by a clinical team with expertise in dementia (Possin, et.al., 2019). We hypothesized that health systems interested in implementing the Care Ecosystem would benefit from an asynchronous online training course to help prepare a dementia‐capable workforce. Method: With a grant from the Merck Foundation, faculty and staff from the UCSF Memory and Aging Center and UC Hastings College of Law developed a series of brief videos (∼10min). Content was adapted for a lay, adult‐learner audience. Multiple choice post‐test questions were written to reinforce content. A Likert scale and an open‐ended question were used to collect feedback for each video. Presentations and quizzes were reviewed by our multidisciplinary team in monthly meetings and over email. Audio was recorded using a smartphone application and spliced with slides into an mp4 video using basic movie editing software. The Canvas Network platform was selected for ease of use, broad availability, and free user account options. Result: The Care Ecosystem Training was released in September 2019 with a link embedded on the Care Ecosystem website (memory.ucsf.edu/care‐ecosystem) and email distribution to three implementation sites. By January 2020, 44 students enrolled in the course, 130 quizzes on 34 topics were completed with an average quality rating of 4.6 (out of 5). Conclusion: The Care Ecosystem Training demonstrates that simple, broadly available technology can be used to increase access to dementia care training. A peer review process helps tailor content for a lay health workforce. The Care Ecosystem Training is designed to be used with the Care Ecosystem Toolkit, and supplemented by clinical observation and case discussions with local clinicians. By prioritizing ease of access for users, the ability to collect user data may be limited. Feedback from quizzes will be used to improve the course.